2019
DOI: 10.3390/agronomy9090480
|View full text |Cite
|
Sign up to set email alerts
|

Soil Extracellular Enzyme Activities and Uptake of N by Oilseed Rape Depending on Fertilization and Seaweed Biostimulant Application

Abstract: The present study has aimed at enhancing the insufficient knowledge of functional soil enzymes properties influenced by inorganic fertilization and biostimulant application to increase the uptake of nitrogen affecting the winter oilseed rape yield. Field experiments were conducted in Poland (53° N, 18° E) in Alfisol (USDA). In this experiment, the NPK rates applied were as follows: high 180 N, 70 P and 160 K 132 N (kg ha−1) or low 144 N, 35 P and 66 K (kg ha−1); fertilization with elemental S 36 or 0 (kg ha−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…High dehydrogenase activity was observed during the full growing season of the pea crop (onset of flowering), and may be associated with increased secretion by the root system during this period, which subsequently leads to increased numbers of microorganisms. Similar results were obtained by Siwik-Ziomek and Szczepanek [72], who analyzed the impact of inorganic fertilization (NPK and S) and the Kelpak biostimulator on dehydrogenase activity in the soil during the cultivation of winter rapeseed. In their study, they observed an increase in dehydrogenase and catalase activity in the period from flowering to ripening.…”
Section: Biochemical Activitysupporting
confidence: 84%
See 1 more Smart Citation
“…High dehydrogenase activity was observed during the full growing season of the pea crop (onset of flowering), and may be associated with increased secretion by the root system during this period, which subsequently leads to increased numbers of microorganisms. Similar results were obtained by Siwik-Ziomek and Szczepanek [72], who analyzed the impact of inorganic fertilization (NPK and S) and the Kelpak biostimulator on dehydrogenase activity in the soil during the cultivation of winter rapeseed. In their study, they observed an increase in dehydrogenase and catalase activity in the period from flowering to ripening.…”
Section: Biochemical Activitysupporting
confidence: 84%
“…It is considered one of the main enzymes with antioxidant activity and works mainly to remove excess hydrogen peroxide (H 2 O 2 ) by converting water and oxygen in all aerobic organisms [82]. Brzezińska et al [72] showed a significant relationship between catalase activity and the oxygenation of soils. The stimulating effect of biostimulators on the activity of this enzyme was demonstrated by Niewiadomska et al [29] in a study conducted during the cultivation of soybean and white lupin, while Stępniewska et al [83] showed significant positive correlations between soil catalase activity and organic matter content, biomass, oxygen absorption, carbon dioxide secretion, as well as dehydrogenase, glucosidase, amidase, and phosphodiesterase activity.…”
Section: Biochemical Activitymentioning
confidence: 99%
“…It reduces their populations and the populations of so-called inductive enzymes, which are secreted into soil by microorganisms. The results of studies conducted by Siwik-Ziomek and Szczepanek [44] and Niewiadomska et al [38] confirmed the diversified dynamics of microbiological changes occurring during the growing season in different weather conditions. It is noteworthy that when the water level in soil is adequate, plants secrete various organic compounds, such as amino acids, carbohydrates and carboxylic acids.…”
Section: Figurementioning
confidence: 66%
“…Our results demonstrated that both maize and rice straw-return treatments (M i R i and M m R i ) significantly increased soil DOC and MBC (Table 3) in the 0-20 cm soil layer. This may be linked to the release of carbon and other organic compounds from the straw, thereby stimulating local microbial activity [46]. Therefore, the enzymes selected in the current study, i.e., urease, cellulase, invertase, and phosphatase, were significantly activated by straw application treatment in the 0-20 cm soil layer (Figure 4).…”
Section: Soil Doc Mbc N Min Available P Exchangeable K and Enzymmentioning
confidence: 90%